Complete Genome Sequencing and Comparative Genomics of Three Potential Probiotic Strains, Lacticaseibacillus casei FBL6, Lacticaseibacillus chiayiensis FBL7, and Lacticaseibacillus zeae FBL8 - Kim, Eiseul; Yang, Seung-Min; Kim, Dayoung; Kim, Hae-Yeong (Frontiers in Microbiology, 2022)
Lacticaseibacillus casei, L. chiayiensis, and L. zeae are very closely related Lacticaseibacillus species. L. casei has long been proposed as a probiotic, whereas studies on functional characterization for L. chiayiensis and L. zeae are some compared to L. casei. In this study, L. casei FBL6, L. chiayiensis FBL7, and L. zeae FBL8 were isolated from raw milk, and their probiotic properties were investigated. Genomic analysis demonstrated the role of L. chiayiensis and L. zeae as probiotic candidates. The three strains were tolerant to acid and bile salt, with inhibitory action against pathogenic bacterial strains and capacity of antioxidants. Complete genome sequences of the three strains were analyzed to highlight the probiotic properties at the genetic level, which results in the discovery of genes corresponding to phenotypic characterization. Moreover, genes known to confer probiotic characteristics were identified, including genes related to biosynthesis, defense machinery, adhesion, and stress adaptation. The comparative genomic analysis with other available genomes revealed 256, 214, and 32 unique genes for FBL6, FBL7, and FBL8, respectively. These genomes contained individual genes encoding proteins that are putatively involved in carbohydrate transport and metabolism, prokaryotic immune system for antiviral defense, and physiological control processes. In particular, L. casei FBL6 had a bacteriocin gene cluster that was not present in other genomes of L. casei, resulting in this strain may exhibit a wide range of antimicrobial activity compared to other L. casei strains. Our data can help us understand the probiotic functionalities of the three strains and suggest that L. chiayiensis and L. zeae species, which are closely related to L. casei, can also be considered as novel potential probiotic candidate strains.